Elite athletes: what lessons for the future can be learned from their responses to the social disruption caused by the COVID-19 pandemic? - Poteko, Kaja; Coakley, Jay; Doupona, Mojca (Frontiers in Sports and Active Living, 2023)
In mid-March 2020, the Covid-19 pandemic was declared, disrupting established routines and impacting every aspect of our lives. Sport as a social phenomenon was no exception. On the one hand, with the suspension and postponement of competitions and the various restrictions, the pandemic seemed to stop time, destroying the previously familiar ways of functioning of the sports sector, and forcing it to constantly reinvent, restructure and adapt. On the other hand, the changed situation highlighted the problems and inequalities that sport had faced long before and that the pandemic had mostly exacerbated, but not caused. In this review article, we identify the lessons and insights the pandemic has brought, especially for elite athletes. Because many scientific articles have emerged in connection with the pandemic, we select and review them according to our focus on elite athletes and summarise their findings. We then use those findings to derive guidelines that can serve top athletes as a tool in potentially similar situations in the future. Our proposed guidelines are divided into macro-, meso-, and micro-social levels, encompassing national and international, organizational and individual perspectives.